A rare presentation of Erdheim Chester disease in a pediatric patient subsequently cured on the LCH III protocol. Issue 1 (6th October 2020) - Gupta, Aditya Kumar; M, Abdul Wajid; Meena, Jagdish P.; ArunRaj, Sreedharan T.; Mridha, Asit; Naranje, Priyanka; Kumar, Rakesh; Seth, Rachna
Abstract: Background: Erdheim Chester disease (ECD) is very rare in pediatrics with no standard treatment guidelines. Here we present the case of a pediatric ECD patient who was cured with a Langerhan cell histiocytosis (LCH) directed chemotherapy protocol. Aim: The aim of the report was to publish this rare presentation of ECD in pediatrics and highlight the complete response obtained to treatment. Methods: The details of the patient were extracted by a retrospective review of her clinical records. Results (Case): An 11 years old girl presented with fever and bone pain. On investigating she had multiple lytic bony lesions scattered throughout her skeleton. A biopsy from one of the bone lesions confirmed the diagnosis to be ECD. ECD is very rare in pediatrics and this case adds to the existing list of 11 previously reported ones. Also, worth mention is the fact that the child presented with isolated skeletal involvement in form of multiple osteolytic lesions. The child was started on the LCH‐III protocol on which she achieved a cure. Conclusion: Lytic bone lesions in a child may be present in ECD. A subset of ECD may have good response to LCH like chemotherapy.